2022
DOI: 10.3390/w14193074
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-Based Model for Flood Shelter Locations and Pedestrian Evacuation Scenarios in a Rural Mountain Catchment in Romania

Abstract: Shelter and evacuation-route planning represents the core of safe and efficient flood management. The methodology detailed in the present study includes an analysis of the suitability of areas for evacuation points, as well as an assessment of the degree of accessibility of those points during evacuation scenarios in small mountainous drainage basins. The analysis is based on water distribution and water-flow increase during the historic 2010 flooding of the Sucevița basin, when the discharge increased in mere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Mountainous areas can quickly concentrate large amounts of water, which are then transported with increased velocities into the river valleys, occupying most or the entire floodplain. In the event of heavy rainfall, these can lead to local floods that can have serious consequences, both for the environment and for the population [98].…”
Section: Discussionmentioning
confidence: 99%
“…Mountainous areas can quickly concentrate large amounts of water, which are then transported with increased velocities into the river valleys, occupying most or the entire floodplain. In the event of heavy rainfall, these can lead to local floods that can have serious consequences, both for the environment and for the population [98].…”
Section: Discussionmentioning
confidence: 99%
“…When populations cannot or will not leave flooding areas, it is important that governments nevertheless provide for ways to address persistent vulnerability. Providing for evacuation routes and flooding shelters can assist in supporting some measures of resilience [55]. A Ghana-located study found that gender was indeed a factor in affecting resilience, with women-headed households being less resilient to flooding events; the study suggested that this variance is due to "family sizes, number of dependent children, intra-household employment levels, and housing characteristics" [56].…”
Section: Floods: Comfort With Calamity?mentioning
confidence: 99%
“…Several authors [25,55,96] referred to evacuation planning, and understanding behavior under such circumstances in future studies would contribute to the resilience literature in practical ways.…”
Section: Conclusion and Opportunities For Further Researchmentioning
confidence: 99%
“…Social vulnerabilities across land tenure categories differ during a disaster, indicating that individuals belonging to a specific tenure category may be vulnerable in one phase of a disaster but not in another. Before a flood occurs, homeowners tend to become more aware of flood hazards [84], understand alerts better [25], and quickly take steps to prevent damage [85], and are less likely to seek emergency shelter [86]. Meanwhile, flood insurance was mainly considered a factor for reducing the impact of floods in studies conducted in developed countries [54].…”
Section: Land Tenure Propertymentioning
confidence: 99%